Report on a transborder spread of carbapenemase-producing bacteria by a patient injured during Euromaidan, Ukraine - J. Hrabák; V. Študentová; V. Adámková; L. Šemberová; P. Kabelíková; D. Hedlová; M. Čurdová; H. Zemlickova; C.C. Papagiannitsis (New Microbes and New Infections, 2015)
Spread of carbapenemase-producing bacteria has been described all over the world. This phenomenon may be accelerated by many factors, including wars and natural disasters. In this report, we described an NDM-1-producing Klebsiella pneumonia ST11 recovered from a patient injured during the Maidan revolution in Ukraine. To our knowledge, this is the first report of a carbapenemase-producing Enterobacteriaceae in Ukraine and one of several reports describing wound colonization/infection of humans injured during war.